Evaluasi Pelaksanaan Pembelajaran Daring dan Hasil Belajar Mahasiswa pada Masa Pandemi Covid-19 - Nurhayati, Faridha; Wibowo, Sapto; Febriyanti, Irma (Jurnal Porkes, 2022)
The purpose of this study is to describe the implementation of online learning and student learning outcomes majoring in Sports Education Sport Science Faculty Universitas Negeri Surabaya during the Covid-19 pandemic. This research is a type of survey research. The population in this study was Sports Education students in the class of 2018, 2019 and 2020 with a technique sampling through purposive sampling, with the number of samples was 117 students. The instruments used are questionnaires via google form and student grades from Siakadu. Data analysis techniques using percentage. Based on the results of the study can be explained;1) related to the understanding of students to the material delivered by lecturers, 43.6% understanding, 41.9% not all understanding and 14.5% not understanding, 2) the use of video tutorials, 53.8% using, 41% not all uses and 5.1% not using,3) online learning assessment satisfaction, 24.8% satisfied, 56.4% quite satisfied and 18.8% dissatisfied, 4) the learning process, 82.1% offline and 19.9% online. While the results of the analysis of student learning value data in the even semester 2020/2021 there are 14 practical subjects and the average grades are A and A-. The conclusion in this study is; 1) the online learning process is going well, because students can understand the material provided by lecturers, 2) the value of average student learning outcomes well, that's A and A-.